Successful story for developing multiple water reuse project and its framework. Issue 3 (December 2014) - Equihua, L.; Rojas, A.; Gonzalez, F.; Canales, A.; Sanz, M. A.; Beltran, F.
Abstract : This article shows how a creative scheme that combines technical capabilities, operation maintenance (O&M) experience and financing models, can increase water availability (from 12 up to 32 Hm 3 /year) and alleviate poverty conditions in a semi-arid region located in central Mexico. Originally, the project was aimed to increase wastewater treatment, but as the water deficit in the region increased to 90 Hm 3 per year (Equihua, Gonzalez and Rojas 2012; Rojas, Equihua and Gonzalez 2012), intensive water reuse became an alternative to water imports from other basins. The San Luis Potosi State Government became a pioneer in Mexico with the first large scale project that accomplished intensive water reuse with different applications or uses (Lazarova, Equihua and Rojas 2013). However, during its first years, the economic viability of the project was uncertain since industrial users and municipal authorities mistrusted each other. At the beginning, the Power Plant Management doubted that the municipality could fulfill a water supply contract with high quality standards and availability, while the municipality had to undertake important investment costs without a long term contract. A third stakeholder had to take the O&M risks in order to give all parties a safe ground to undertake the project. For the last 7 years, the Tenorio Project has proven its value, and the Power Plant accepted the alternative source of water and agreed to pay a tariff on a per cubic meter supplied. The Power Plant also decided to replace all the cooling make-up with reclaimed water. Nowadays, power production is demanding a substantial upgrade of the project in order to substitute the entire supply of groundwater in the processes. The Power Plant has agreed to exchange its original groundwater rights with the municipality to consolidate a new water source for the City of San Luis Potosi (SLP). At the same time, the municipality guarantees the reclaimed water supply with proven reliability and flexibility through a private operator. At this stage, the Project would augment water availability for the SLP Metropolitan area by 12 Hm 3 /year and could be scaled up to 34·5 Hm 3 /year with the incorporation of new wells and the addition of a re-injection phase with another 2·5 Hm 3 /year, which could be implemented in the future.